Inside the Black Box of Jail: Barriers to Change at the Ottawa-Carleton Detention Centre - Maadarani, Mariah (Université d'Ottawa / University of Ottawa, 2020)
The Ottawa-Carleton Detention Centre (OCDC) is notorious for its austere conditions of confinement and human rights violations. In response to widespread criticism, the Ontario provincial government created a dedicated task force in 2016 to address longstanding issues at the jail. To date, little research has examined how OCDC has maintained these deplorable conditions of confinement despite concerted effort to improve them. Drawing on Mathiesen’s (1990) neutralization techniques, this thesis reveals the tactics used by government officials and jail functionaries to maintain the status quo at OCDC and stifle transformative change by comparing task force recommendations with their ensuing implementation. Through a qualitative content analysis of the OCDC task force progress reports, trend analyses, Ombudsman, Community Advisory Board, Independent Review of Corrections, and Jail Accountability & Information Line reports documenting issues at OCDC, I demonstrate how the Ontario provincial government and OCDC administration (a) refer to competing demands, higher authority, policy and procedure, or safety and security as excuses for not instituting changes, (b) define policy alternatives as irrelevant or impossible to implement, (c) postpone implementation of measures for not being developed enough or possible now, as well as (d) puncture and (e) absorb policy alternatives to uphold the status quo and impede transformative change. In doing so, I expose the provincial penal system’s proclivity to ‘finish’ (Mathiesen, 1974) alternatives that threaten the current system, thereby gutting new ideas of their ability to generate meaningful social change. The insights provided by this thesis help lay the groundwork for future critical criminological research to examine the barriers to social change in the penal field on a sub-national, national, and international scale.
Keywords: Ottawa-Carleton Detention Centre; Jail; Social change; Neutralization techniques; Conditions of confinement; Prisoners' Rights